1988
DOI: 10.1097/00007890-198804000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Epstein-Barr Virus Infection and Associated Lymphoproliferative Syndrome After Transplantation and Its Manifestations in Children

Abstract: Twenty cases of Epstein-Barr virus (EBV)-associated lymphoproliferative syndrome (LPS), defined by the presence of EBV nuclear antigen and/or EBV DNA in tissues, were diagnosed in 1467 transplant recipients in Pittsburgh from 1981-1985. The frequency of occurrence in pediatric transplant recipients was 4% (10/253), while in adults it was 0.8% (10/1214) (P less than .0005). The frequency of LPS in adults declined after 1983 coincidental with the introduction of cyclosporine monitoring. However there was no appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
164
1
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(173 citation statements)
references
References 22 publications
6
164
1
2
Order By: Relevance
“…Indeed, it has been observed that EBVseronegative recipients of organ allografts are at increased risk of BLPD. 39 Screening of donors and recipients for EBV serostatus is not routinely performed prior to HSCT, therefore the effect of EBV serostatus on the development of BLPD is unknown. It has been claimed that antiviral prophylaxis with acyclovir prevents BLPD, 1 but our experience does not support this.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been observed that EBVseronegative recipients of organ allografts are at increased risk of BLPD. 39 Screening of donors and recipients for EBV serostatus is not routinely performed prior to HSCT, therefore the effect of EBV serostatus on the development of BLPD is unknown. It has been claimed that antiviral prophylaxis with acyclovir prevents BLPD, 1 but our experience does not support this.…”
Section: Discussionmentioning
confidence: 99%
“…The observed differences may be related to the amount of lymphoid tissue transplanted, and the level of immunosuppressive therapy required to prevent transplant rejection [2][3][4][5] . EBV-related PTLD occurs more frequently in children owing to primary infection, while its occurrence in adults is a result of either primary infection or reactivation 6,7 . Presentation can vary from polyclonal reactive hyperplasia of B-cells, to monoclonal or polyclonal lymphomas.…”
Section: Epstein-barr Virus (Ebv) Is a Deoxyribonucleic Acid (Dna)mentioning
confidence: 99%
“…When transplants are performed in young patients, there is a high likelihood that they will be seronegative for CMV and EBV and therefore susceptible to primary infections, which are more severe than infections due to reactivation. 6,7 Donor-related issues represent another set of pretransplant factors. Transplant recipients are at risk for acquiring infections that may be active or latent within the donor organ.…”
Section: Pretransplant Factorsmentioning
confidence: 99%
“…6,13 However, the use of CMV prophylaxis has resulted in shifting the time of presentation of CMV disease so that some patients will present with this infection after 180 days. The intermediate period is also when patients begin to present with EBV-associated PTLD 7 and Pneumocystis jirovecii pneumonia (PCP). 13 …”
Section: Early Infections (0-30 Days)mentioning
confidence: 99%